Injury‐induced MRP8/MRP14 stimulates IP‐10/CXCL10 in monocytes/macrophages. Issue 1 (23rd October 2014) - Wang, Juan; Vodovotz, Yoram; Fan, Liyan; Li, Yuehua; Liu, Zheng; Namas, Rami; Barclay, Derek; Zamora, Ruben; Billiar, Timothy R.; Wilson, Mark A.; Fan, Jie; Jiang, Yong
Abstract : Trauma/hemorrhagic shock is associated with morbidity and mortality due to dysregulated inflammation, which is driven in part by monocytes/macrophages stimulated by injury‐induced release of damage‐associated molecular pattern (DAMP) molecules. MRP8/MRP14 is an endogenous DAMP involved in various inflammatory diseases, though its mechanism of action is unclear. Circulating MRP8/MRP14 levels in human blunt trauma nonsurvivors were significantly lower than those of survivors ( P < 0.001). Human monocytic THP‐1 cells stimulated with MRP8/MRP14 expressed the chemokine IFN‐γ inducible protein 10 (IP‐10)/CXCL10. Circulating IP‐10 levels in human blunt trauma patients were correlated positively with MRP8/MRP14 levels ( r = 0.396, P < 0.001), and were significantly lower in trauma nonsurvivors than in survivors ( P < 0.001). We therefore sought to determine the mechanisms by which MRP8/MRP14 stimulates IP‐10 in monocytes/macrophages, and found that induction of IP‐10 by MRP8/MRP14 required Toll‐like receptor 4 and TRIF but not MyD88. Full induction of IP‐10 by MRP8/MRP14 required synergy between the transcription factors NF‐κB and IFN regulatory factor 3 (IRF3). The receptor for IP‐10 is CXCR3, and MRP8/MRP14‐induced chemotaxis of CXCR3 + cells was dependent on the production of IP‐10 in monocytes/macrophages. Furthermore, in vivo study with a mouse trauma/hemorrhagic shock model showed that administration of neutralizing antibody against MRP8 prevented activation of NF‐κB and IRF3 as well as IP‐10 production. Thus, the current study identified a novel signaling mechanism that controls IP‐10 expression in monocytes/macrophages by MRP8/MRP14, which may play an important role in injury‐induced inflammation.—Wang, J., Vodovotz, Y., Fan, L., Li, Y., Liu, Z., Namas, R., Barclay, D., Zamora, R., Billiar, T. R., Wilson, M. A., Fan, J., Jiang, Y., Injury‐induced MRP8/MRP14 stimulates IP‐10/CXCL10 in monocytes/macrophages. FASEB J. 29, 250–262 (2015). www.fasebj.org